Measurement and Enhancement of Environmental Responsibility Level of an Energy Enterprise in the Context of Energy Transformation - Shanshan Hou; Liang Tang; Jiuyang Xue; Jingnan Lu (Discrete Dynamics in Nature and Society)
Energy transformation requires energy producers to pursue energy conservation and emission reduction, control greenhouse gas (GHG) emissions, and produce and supply clean low-carbon energy. Based on the principle of balanced scorecard, this paper selects the data on China Shenhua Energy Company Limited (China Shenhua) of 2015–2019, systematically analyzes the influence of energy transformation on environmental protection effect of energy enterprises, and measures the environmental responsibility level (ERL). The results show that, in the context of energy transformation, Chine Shenhua always attaches great importance to ecoenvironment protection, vigorously develops clean, safe, and efficient energy, implements key tasks like green mine construction and ultra-low emission upgrading, promotes pollution control and ecoenvironment governance, takes measures of energy conservation and emission reduction, and continuously steps up the level of carbon emissions control, thereby steadily improving ecological civilization.